Initial and continued adherence to wearing appropriate footwear in people with diabetic foot disease: results of a pilot study - Aristomenis Kossioris; Nicholas Tentolouris; Venetsana Kyriazopoulou; Chariclia V Loupa; Georgia Markou; George E Marakomichelakis; Eftychia Zouridaki; Minos Tyllianakis (Ene, 2017)
Background: For the prevention and healing of diabetic foot ulcers, appropriate footwear or medical devices are utilized. However, initial and continued adherence of patients with diabetes-related foot problems in using such therapeutic means, is not satisfactory. bjective: To explore initial and continued adherence to wearing appropriate footwear in people with diabetic foot disease. Methods: A cross-sectional study was conducted, from March to November 2016, at general and special hospitals in Athens, Greece. Forty-one outpatients with type 1 and 2 Diabetes Mellitus, with medical recommendation for wearing appropriate footwear, participated. A structured quantitative interview guide and medical measuring instruments were used. For data analysis, descriptive and inferential statistic methods were applied using the IBM SPSS 24 software package. Results: Suitable for diabetes footwear were worn from the 56.1% of participants. The 27.3% of risk patients wore their preventive shoes ≥60% (≥9.6 hours) of daytime. The patients with active foot ulcers wore appropriate footwear at a lesser percentage than the ones at risk (44.4% versus 78.6%, χ2(1) =4.36, p=0.037; OR 4.58, 95% CI 1.04-20.24, p=0.045) and the initially adherent group had significantly subordinate Visual Analogue Scale score in relation to the satisfaction from the footwear price (Mdn=5.00) than the one that was not initially adherent (Mdn=8.00), U=97.00, z=-2.36, p=0.019, r=-.38. Conclusion: For the enhancement of initial and continued adherence in wearing appropriate footwear, health care professionals could pay more attention to the education of patients with active foot ulcers, underling the importance of using right shoes. Additionally, they could provide patients with multiple price options concerning their footwear (e.g. by suggesting effective and affordable products).